2008
DOI: 10.1111/j.1365-2559.2007.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent prognostic value of the basal‐like phenotype of breast cancer and associations with EGFR and candidate stem cell marker BMI‐1

Abstract: Basal-like features and lymph node status were strong and independent prognostic factors in this population-based series of breast cancer. Neither EGFR nor BMI-1 had significant prognostic impact, whereas EZH2 expression was associated with decreased survival. BMI-1 was inversely related to basal-like factors, and a stem cell phenotype of the basal-like subgroup could not be verified by this marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 70 publications
(133 reference statements)
5
36
1
Order By: Relevance
“…For other types of cancer, some studies demonstrated that overexpression of Bmi1 was correlated with a poor prognosis [42][43][44] ; however, others reported that loss of Bmi1 expression was correlated with an aggressive phenotype, indicating a protective role of the Bmi1 protein. [45][46][47] Abundant expression of Bmi1 in normal bronchial epithelial cells in the current study and in a previous report 19 and low Bmi1 expression in the majority of tumor cells suggest that Bmi1 may have a protective role in NSCLC. The role of Bmi1 in lung cancer remains to be defined.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Alsupporting
confidence: 79%
“…For other types of cancer, some studies demonstrated that overexpression of Bmi1 was correlated with a poor prognosis [42][43][44] ; however, others reported that loss of Bmi1 expression was correlated with an aggressive phenotype, indicating a protective role of the Bmi1 protein. [45][46][47] Abundant expression of Bmi1 in normal bronchial epithelial cells in the current study and in a previous report 19 and low Bmi1 expression in the majority of tumor cells suggest that Bmi1 may have a protective role in NSCLC. The role of Bmi1 in lung cancer remains to be defined.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Alsupporting
confidence: 79%
“…This is in line with our recent studies of breast cancer and other tumours (Bachmann et al, 2008;Engelsen et al, 2008). The frequency of BMI-1 expression (25%) was lower than those found in other studies (43 -62%) (Kim et al, 2004;Arnes et al, 2008;Choi et al, 2009). Others have found different results, BMI-1 expression being associated with more aggressive tumours (Glinsky et al, 2005;Silva et al, 2007).…”
Section: Discussioncontrasting
confidence: 36%
“…Still, BMI-1 has been linked to mammary carcinogenesis in some previous studies (Dimri et al, 2002;Datta et al, 2007). Although some find BMI-1 expression to be associated with a favourable prognosis (Kim et al, 2004;Arnes et al, 2008;Choi et al, 2009), others have reported the opposite (Glinsky et al, 2005;Silva et al, 2007).…”
mentioning
confidence: 94%
See 2 more Smart Citations